2020
DOI: 10.18699/vj20.666
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenophora tritici-repentis population structure in the Republic of Kazakhstan and identification of wheat germplasm resistant to tan spot

Abstract: Pyrenophora tritici-repentis is a causative agent of tan spot in wheat. In recent years, there has been an increasing spread and harmfulness of wheat tan spot. The aim of the research was to study the racial composition of the P. tritici-repentis population in the Republic of Kazakhstan. A collection of 30 common wheat accessions, including promising lines and cultivars from Kazakhstan and CIMMYT–ICARDA, was assessed for resistance to P. triticirepentis in a greenhouse and characterized using the Xfcp623 molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(29 reference statements)
2
11
0
Order By: Relevance
“…Lamari et al (1998) were the first to report race 5 in Algeria, and this race has since been reported in Canada (Strelkov et al, 2002), the United States of America (Ali et al,1999), Syria and Azerbaijan (Lamari et al, 2005b). In contrast, race 6 was found in Algeria and Morocco (Strelkov et al, 2002;Benslimane, 2018;Gamba et al, 2017), while races 7 and 8 were found only in the Middle East, Caucasus and Algeria, and Kazakhstan in 2018 and 2020 (Kokhmetova et al, 2020b;Benslimane, 2018, Ouaar et al, 2022. In 2021, in the North Caucasus region of Russia, races 1, 3 and 4 were identified (Kremneva et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Lamari et al (1998) were the first to report race 5 in Algeria, and this race has since been reported in Canada (Strelkov et al, 2002), the United States of America (Ali et al,1999), Syria and Azerbaijan (Lamari et al, 2005b). In contrast, race 6 was found in Algeria and Morocco (Strelkov et al, 2002;Benslimane, 2018;Gamba et al, 2017), while races 7 and 8 were found only in the Middle East, Caucasus and Algeria, and Kazakhstan in 2018 and 2020 (Kokhmetova et al, 2020b;Benslimane, 2018, Ouaar et al, 2022. In 2021, in the North Caucasus region of Russia, races 1, 3 and 4 were identified (Kremneva et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The race population structure of P. tritici-repentis in Kazakhstan has had large fluctuations in recent years (Kokhmetova et al, 2016b., Kokhmetova et al, 2020b. Population structure and race composition of the pathogen has been studied in many geographic regions in the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…f. sp. tritici and leaf rust caused by Puccinia triticina Erikss [2-8], as well as leaf spot diseases (tan spot and Septoria) [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for the reduction in the yield of wheat in Kazakhstan is the disease with airborne infection. Dominant position, as a part of the pathogenic complex of wheat in Kazakhstan, is taken by rusts (yellow, stem, and leaf rust) [2][3][4][5], as well as leaf spot diseases (tan spot and Septoria) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%